The Ukrainian reading public in the 1920s: real, implied, and ideal. Issue 2 (2nd April 2016) - Shkandrij, Myroslav
ABSTRACT: The reading public was discussed in the Soviet Ukrainian press during the 1920s, at a time when the drive to eliminate illiteracy and implement Ukrainization was scoring increasing successes. Sociological studies of the "real" reader indicated strong preferences for pre-revolutionary authors and foreign writers in translation. Under pressure from Moscow, in the late 1920s Mykola Skrypnyk, the Commissar for Education, and the literary theorist Kost' Dovhan' changed the rhetoric advocating Ukrainization, stressing its proletarian content. They supported the concept of an "implied" working-class reader who read Ukrainian and was simultaneously committed to developing socialism and a "proletarian" culture. However, many sophisticated writers pitched their work to an "ideal" reader, whom they imagined as the end-product of Ukrainization – a culturally literate, urban, and critically thinking consumer. The three ways of conceptualizing the consumer clashed, as the Ukrainization policy went through two major shifts during the period of the first five-year plan (1928–33). Ideologists, educators, and writers adapted to these shifts by redefining the way they conceptualized the reader.